Knowledge of nursing students on vasculogenic lesions - Raísa Leocádio Oliveira; Lariza Martins Falcão; Elaine Cristina Carvalho Moura; Fernanda Valeria Silva Dantas Avelino; Raylane da Silva Machado (Rev Rene)
Objective: to assess the knowledge of nursing students on vasculogenic lesions. Methods: cross-sectional and descriptive study conducted in four higher education institutions. Researchers applied a questionnaire to 106 nursing students, which was composed of variables, such as school situation, prior contact and knowledge of students on the subject. Results: the mean score on the characteristics of vasculogenic lesions was higher among public institutions academic (33.0%), among those who reported having provided nursing care for patients with these lesions (37.7%) and among those who claimed to know the difference between venous lesions and arterial lesions (25.5%). The higher amount of correct answers on venous lesions was related to the coloration in perilesional area (74.5%); and on arterial lesions, regarding habits and underlying diseases (67.0%). Conclusion: academics who have practical experience in the care of patients with vasculogenic lesions during undergraduate course had higher theoretical knowledge on the subject.